Towards Islamic Pedagogy By Exploring The Applications Of Educational Technology - Yunita, Yunita; Mulyadi, Mulyadi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
Islamic education has long been an integral part of the Muslim intellectual tradition. However, new challenges and opportunities emerge in strengthening Islamic pedagogy in the current digital era. This article aims to explore how integrating technology in the context of Islamic education can enrich learning experiences and develop pedagogy connected to Islamic values. Through a literature review, we explore various educational technology applications that can be used to improve Islamic-based learning. We highlight the implementation of technology, such as interactive learning applications, e-learning platforms, and social media, that can facilitate discussion and collaboration between students and educators. In addition, we analyze Islamic pedagogical principles that can be integrated into developing and using educational technology. Concepts such as active participation, collaborative learning, and student-centered learning experiences are considered in the context of Islamic values such as justice, compassion, and example. Through this approach, technology in Islamic education will increase the efficiency and effectiveness of learning and respect and strengthen the spiritual and moral values that underlie Islamic education. Future research can explore the practical implementation of Islamic pedagogy connected to technology in formal and non-formal educational contexts and evaluate its impact on achieving the goals of Islamic education.